COMMUNITY EMPOWERMENT IN PINEAPPLE AGROINDUSTRY WASTE UTILIZATION AS AN INGREDIENT OF SNACKS IN SUBANG DISTRICTS - Annis Catur Adi; Mahmud Aditya Rifqi; Deandra Ardya Regitasari; Vidya Anggarini Rahmasari; Wizara Salisa; Heni Rachmawati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background:The development of agro-industry in Indonesia remains facing many obstacles. In addition to the environmental wasteproblem, the low ability to process products leads to their low added value, as faced bypineapple agro-industry associationin Barokah Agro Lestari (BAL). This community service activity is important to improve beneficial and economical value of pineapple agro-industry. Purpose: This activity aims to reduce the environmental burdenof pineapple agro-industry by product by implementing technology to give its added value as well as providing a healthy snack alternative for society. Method: This community service activity is carried out through counseling, training and education related to waste product of pineapple. These activities included the preparation phase, the selection of organic waste of pineapple, bioactive component testing, testing of nutrients and food formulation. Results:The community service program was conducted at PT Karya Masyarakat Mandiri in Subang District and attended by 30 pineapple farmers from Cirangkong village, gathered in Barokah Agro Lestari (BAL). Training was done by administering stages of activity systemically, exposure of the material using visual methods, cooking demonstration for the training activities of processing and product development. Conclusion: Community service activities and training in processing the pineapple stem waste can be a means of empowering local communities. Processing organic waste into food products help improving the community skills and motivation for business development through organic waste treatment.